An exploratory study on the potential impact of internet on organizations and individuals in Singapore - Foo, Eliza Sing Lam (2014)
Internet is gaining popularity among users world-wide as an information "superhighway". With the recent introduction of Singnet, Technet and other local networks, Singapore individuals have also jumped onto the bandwagon of Internet users. The establishment of these networks promotes awareness and usage of Internet which falls in line with Singapore's IT2000 plan to be an intelligent island.